A hybrid electric field assisted vacuum membrane distillation method to mitigate membrane fouling. Issue 32 (16th May 2018) - Huang, Qinglin; Liu, Huan; Wang, Yafeng; Xiao, Changfa
Abstract : EVMD with a PTFE electro-catalytic membrane can effectively mitigate membrane fouling. Abstract : We proposed a novel method for vacuum membrane distillation (VMD) called Electric Field Assisted Vacuum Membrane Distillation (EVMD) that can be used to mitigate membrane fouling. A biaxial stretching polytetrafluoroethylene (PTFE) membrane was utilized as the base membrane, and multi-walled carbon nanotubes (MWCNTs) or a mixture of MWCNTs/graphene as a conductive substrate. During EVMD, the conductive PTFE membrane acted as the cathode while a stainless-steel wire mesh surrounding the conductive membrane acted as the anode. The effect of the per unit area loading mass (PUALM) of the conductive substrate on the membrane performance were investigated. Results revealed that for a PUALM of 10 g m −2, the PTFE membrane not only exhibited excellent conductivity but also showed a high rate of gas flux. Doping graphene into the MWCNT conductive substrate led to the formation of nano-channels which served to improve the membrane distillation flux and the membrane hydrophobicity. The effects of the electric field strength as well as humic acid (HA) concentration on the antifouling performance during EVMD were also investigated. Results showed that during EVMD, the PTFE conductive membrane exhibited the best antifouling ability using an intermittent electric field with a field strength of 1.0 V cm −1 .